2017
DOI: 10.18632/oncotarget.22900
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing-based microRNA profiling of mice testis subjected to transient heat stress

Abstract: This study aimed to investigate the role of microRNA (miRNA) in heat stress-induced spermatogenic impairment. Testes from 15 adult ICR mice subjected to testicular hyperthermia at 43°C for 30 min and from 15 control mice were collected and pooled into 3 samples. Isolated RNA from these samples was subjected to small RNA high-throughput sequencing, and differentially expressed miRNAs were identified and validated using RT-PCR. The identified miRNAs were further subjected to Gene Ontology and KEGG analyses, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…For example, Guo et al (2017) reported that miR‐423 was a potential therapeutic target for the premature ovarian insufficiency leading to infertility. Rao et al (2017) reported that miR‐423 participated in the regulation of germ cell apoptosis, which became a potential candidate target in the process of male infertility. Low sperm motility is a frequent reason for fertilization failure of in vitro fertilization (IVF).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guo et al (2017) reported that miR‐423 was a potential therapeutic target for the premature ovarian insufficiency leading to infertility. Rao et al (2017) reported that miR‐423 participated in the regulation of germ cell apoptosis, which became a potential candidate target in the process of male infertility. Low sperm motility is a frequent reason for fertilization failure of in vitro fertilization (IVF).…”
Section: Introductionmentioning
confidence: 99%
“…To date, roughly 500–1,000 miRNAs (both conserved and nonconserved) are found in the human genome that targeting >30% of human protein‐coding genes (Bentwich et al, 2005; Yang et al, 2017). Recent studies have revealed that specific miRNA contributes to the modulation of oxidative stress and their irregular results due to the impairment in spermatogenesis of infertile males (Kotaja, 2014; M. Rao et al, 2017). This is evident that miRNA‐122a plays an important role in germ cell development.…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in the regulation of cell proliferation and apoptosis. In our previous study, we sequenced the miRNA of mouse testes after heat stress 9 and, for the first time, found that miR‐128‐3p expression is downregulated after heat stress. Previous research on miR‐128‐3p has mainly focused on tumor‐related diseases; few reports of miR‐128‐3p in relation to the reproductive system are available.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that microRNAs (miRNAs) play an important role in regulating spermatogenesis, especially spermatogenic meiotic division, apoptosis, and Sertoli cell function 6‐8 . In previous experiments, our team 9 identified some differentially expressed miRNAs (eg, miR‐449a‐3p, miR‐92a‐1‐5p, miR‐423‐3p, and miR‐128‐3p) after testicular heat stress, which are closely related to germ cell apoptosis and are involved in multiple pathways (eg, ribosomal, HIF‐1, and MAPK pathways). These pathways may also be critical in heat stress‐induced testicular injury.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation